A Correlational Study on Personal Development Skills in Relation to Communication Confidence and Interpersonal Communication Among TVET Students (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Malaysia is rapidly evolving in educational and economic landscape with a social and technical workforce. The Technical and Vocational Education and Training (TVET) sector is crucial to the development of graduates who are not only skilled in technical skills but also able to work in a team-oriented environment. This study aims to examine the relationship between personal development skills, communication confidence, and interpersonal communication among students enrolled in Technical and Vocational Education and Training (TVET) programs at Politeknik Mukah. This study employed a quantitative correlational approach, and a total of 326 TVET students participated in the study. The results revealed significant and strong positive correlations between communication confidence and interpersonal communication with personal development skills. These findings suggest that TVET institutions and industrial cooperation should incorporate strategies in developing programs that could strengthen personal development skills among TVET students. In conjunction with Industry 4.0, the Technical and Vocational Education and Training (TVET) sector must attain holistic growth, and this will align to the Sustainable Development Goal 4 (SDG 4), which encourages the provision of quality education and Sustainable Development Goal 8 (SDG8) which promotes decent work and economic growth.